2016
DOI: 10.2217/pgs.15.177
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Pharmacogenetic Research to Guide Tobacco Cessation by Patients, Providers and Leaders in a Tribal Healthcare Setting

Abstract: Aim: Describe patients,' providers' and healthcare system leaders' perceptions of pharmacogenetic research to guide tobacco cessation treatment in an American Indian/Alaska Native primary care setting. Materials & methods: This qualitative study used semistructured interviews with 20 American Indian/Alaska Native current or former tobacco users, 12 healthcare providers and nine healthcare system leaders. Results: Participants supported pharmacogenetic research to guide tobacco cessation treatment provided that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Our study also found mixed views among participants about sharing their pharmacogenomic information with pharmacists, in contrast with other studies where ≥ 70% of individuals would share their results with their pharmacists [10,13]. Additionally, we found that both genotyped and non-genotyped participants held concerns over insurance coverage, employment discrimination, and cost implications of pharmacogenomic-guided care, all of which have similarly been reported in previous studies [9,1113,2325]. As cost/reimbursement considerations remain one of the greatest barriers to more universal adoption of pharmacogenomics, these considerations will need to be addressed via practice-based or institutional standards during early phases of implementation.…”
Section: Discussionsupporting
confidence: 57%
“…Our study also found mixed views among participants about sharing their pharmacogenomic information with pharmacists, in contrast with other studies where ≥ 70% of individuals would share their results with their pharmacists [10,13]. Additionally, we found that both genotyped and non-genotyped participants held concerns over insurance coverage, employment discrimination, and cost implications of pharmacogenomic-guided care, all of which have similarly been reported in previous studies [9,1113,2325]. As cost/reimbursement considerations remain one of the greatest barriers to more universal adoption of pharmacogenomics, these considerations will need to be addressed via practice-based or institutional standards during early phases of implementation.…”
Section: Discussionsupporting
confidence: 57%
“…Communicating these practices of transparency helps to solidify trust with the ANAI community by showing how researchers are working to include the ANAI community in the research process as early as possible. The views shared in the community deliberation echo participant feedback from ANAI community focus groups from over a decade ago [12,43], and other qualitative inquiry more recently conducted at SCF [13,15,17,25].…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, genetic research in ANAI communities must address areas of known disparities, clearly delineate potential health benefits and risks, and provide adequate protections against individual and group harm [11,12]. ANAI communities expect transparent research practices that include tribal oversight and approval of the research, a robust informed consent process, and dissemination of study updates and findings throughout the research project [13][14][15][16][17]. Research partnerships that have taken the time to meet these expectations resulted in equitable partnerships with novel genetic findings [14,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 20 permanent SCF Research Department employees, 15 have AN/AI heritage, not counting available AN/AI intern positions at the pre-baccalaureate, baccalaureate, and graduate levels. In further engagement with the community, the SCF Research Department conducted qualitative research asking AN/AI people to consider the cultural and ethical implications of different types of research, such as genetic research, and to comment upon research processes like informed consent, data and specimen storage, and return of results (Avey et al, 2016; Hiratsuka, Brown, & Dillard, 2012; Shaw, Robinson, Starks, Burke, & Dillard, 2013; Starks, Shaw, Hiratsuka, Dillard, & Robinson, 2015; Woodahl et al, 2014). Subsequently, the SCF Research Department implemented improvements in the informed consent process and the storage of data and specimens in local repositories with AN oversight (Hiratsuka, Brown, & Dillard, 2012; Hiratsuka, Brown, Hoeft, & Dillard, 2012).…”
Section: Southcentral Foundation’s Research Departmentmentioning
confidence: 99%